Inhibition of Innate Co‐Receptor TREM‐1 Signaling Reduces CD4+ T Cell Activation and Prolongs Cardiac Allograft Survival. Issue 5 (6th March 2013) - Schiechl, G.; Brunner, S. M.; Kesselring, R.; Martin, M.; Ruemmele, P.; Mack, M.; Hirt, S. W.; Schlitt, H. J.; Geissler, E. K.; Fichtner‐Feigl, S.
<x xml:space="preserve">Abstract</x> The innate receptor "triggering‐receptor‐expressed‐on‐myeloid‐cells‐1" (TREM‐1) enhances downstream signaling of "pattern recognition receptor" (PRR) molecules implicated in inflammatory responses. However the mechanistic role of TREM‐1 in chronic heart rejection has yet to be elucidated. We examined the effect of TREM‐1+ antigen‐presenting cells (APC) on alloreactive CD4+ lymphocytes. Bm12 donor hearts were transplanted into wild‐type MHC‐class‐II‐mismatched C57BL/6J recipient mice. Progressive allograft rejection of bm12‐donor hearts with decreased organ function, severe vasculopathy and allograft fibrosis was evident within 4 weeks. TREM‐1+CD11b+MHC‐II+F4/80+CCR2+ APC and IFNγ‐producing CD4+ cells were detected during chronic rejection. Peptide inhibition of TREM‐1 attenuated graft vasculopathy, reduced graft‐infiltrating leukocytes and prolonged allograft survival, while being accompanied by sustained low levels of CD4+ and CD8+ cell infiltration. Remarkably, temporary inhibition of TREM‐1 during early immune activation was sufficient for long‐term allograft survival. Mechanistically, TREM‐1 inhibition leads to reduced differentiation and proliferation of IFNγ‐producing Th1 cells. In conclusion, TREM‐1 influences chronic heart rejection by regulating the infiltration and differentiation of CD4+ lymphocytes.